2014
DOI: 10.1292/jvms.14-0218
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Glomerular Filtration Rate in Cynomolgus Monkeys (<i>Macaca fascicularis</i>)

Abstract: To estimate the glomerular filtration rate (GFR) in cynomolgus monkeys (Macaca fascicularis), a three-blood-sample method using iodixanol was assessed in comparison with the conventional multisample strategy using inulin. Iodixanol and inulin were coadministered intravenously 40 mg I/kg and 50 mg/kg, respectively, to male monkeys, followed by blood collection 60, 90 and 120 min later. A close correlation (r=0.96) was noted between the GFR values estimated by both methods. In clinically healthy monkeys, the bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…It is also important to add that the shape of the CL vs. protein size relationship discovered by us should be taken as an approximation of the true relationship, and this relationship should become more robust as we generate more data (especially in the extreme molecular weight ranges) in multiple animal species going forward. Nonetheless, it was found that the intercept of the CL vs. molecular weight relationship for each animal species (0.27 ml/min for mouse, 1.52 ml/min for rat, 4.53 ml/min for rabbit, 15.5 ml/min for monkey, and 96 ml/min for human) was very close to the reported GFR values for each animal species (0.28 ml/min for mouse (15), 1.6 ml/min for rat (17), 5.1 ml/min for rabbit (18), 19 ml/min for monkey (19), and 126 ml/min for human (17)). This suggests that the clearance values predicted by the CL vs. molecular weight relationship are realistic and physiologically relevant for all the animal species evaluated.…”
Section: Discussionsupporting
confidence: 84%
“…It is also important to add that the shape of the CL vs. protein size relationship discovered by us should be taken as an approximation of the true relationship, and this relationship should become more robust as we generate more data (especially in the extreme molecular weight ranges) in multiple animal species going forward. Nonetheless, it was found that the intercept of the CL vs. molecular weight relationship for each animal species (0.27 ml/min for mouse, 1.52 ml/min for rat, 4.53 ml/min for rabbit, 15.5 ml/min for monkey, and 96 ml/min for human) was very close to the reported GFR values for each animal species (0.28 ml/min for mouse (15), 1.6 ml/min for rat (17), 5.1 ml/min for rabbit (18), 19 ml/min for monkey (19), and 126 ml/min for human (17)). This suggests that the clearance values predicted by the CL vs. molecular weight relationship are realistic and physiologically relevant for all the animal species evaluated.…”
Section: Discussionsupporting
confidence: 84%
“…The Vd ss was estimated to be 181 mL/kg, indicating the extravascular distribution of MGS0008. Similar to the observation in rats, 96.4% of the administered dose was excreted as the unchanged form in urine within 48 hours, and the CL renal was calculated to be 124 mL/h/kg, which was approximately equal to the CL total and GFR in monkeys (184 ± 30 mL/h/kg) 16. Unlike the observations in rats, an oral dose of MGS0008 in monkeys resulted in sustained plasma concentrations at low levels during the observation period up to 24 hours, and the oral bioavailability of MGS0008 was calculated to be only 3.8%.…”
supporting
confidence: 68%
“…Blood (0.5 ml) was withdrawn before and 60, 90 and 120 min after the tracer injection. The dose of inulin (50 mg kg −1 ) or iodixanol (40 mg I kg −1 ) and sampling points were selected based on the previous monkey study (Iwama et al ., ). In this study, healthy means non‐treated monkeys at preadministration.…”
Section: Methodsmentioning
confidence: 97%
“…Here, we recently reported that serum clearance of the isotonic, nonionic, dimeric, radiographic contrast medium iodixanol using a multisample strategy without urine collection was a ready‐to‐use tool for screening the GFR in cynomolgus monkeys (Iwama et al ., ). Iodixanol is physiologically inert, stable in plasma, and freely filtered at the glomerulus without secretion or reabsorption in the renal tubules (Svaland et al ., ; Heglund et al ., ; Jacobsen et al ., ).…”
Section: Introductionmentioning
confidence: 97%